Topical Caspofungin for Treatment of Keratitis Caused by Candida albicans in a Rabbit Model - Goldblum, David (American Society for Microbiology, 2005)
Candida albicans is the most frequent cause of fungal keratitis in temperate regions. Caspofungin has potent activity against Candida spp. in a variety of clinical settings. Little is known, however, about its activity against fungal keratitis. We compared the efficacy of topical caspofungin with that of topical amphotericin B (AMB) in a rabbit model of experimental keratomycosis. Keratitis was induced with a standardized inoculum of Candida albicans (SC 5314) placed on the debrided cornea. Twenty-four hours after infection, animals were randomly assigned to treatment with 0.15% caspofungin, 0.5% caspofungin, 0.15% AMB, and a saline control (n = 12 rabbits in each group). For the first 12 h, treatment was repeated every 30 min and, after a 12-h pause, was resumed at hourly intervals for another 12 h. The animals were examined and killed 12 h after administration of the last dose. Treatment effects were evaluated by clinical assessment, fungal culture, and histopathology. Drug treatment significantly reduced corneal fungal recovery from 3.78 log(10) CFU in saline-treated animals to 2.97, 1.76, and 1.18 log(10) CFU in animals treated with 0.15% caspofungin, 0.5% caspofungin, and 0.15% AMB, respectively. By histopathology, the mean hyphal density was significantly lower in the corneas of treated animals than in those of the controls; there was no difference in hyphal densities between the different treatment groups. The depth of corneal invasion was not significantly reduced by the antifungal treatments. By clinical assessment, keratitis progressed in animals treated with saline, whereas disease progression was inhibited by all drug treatment regimens. In our rabbit model, 0.5% caspofungin was as effective as 0.15% AMB for the topical treatment of Candida keratitis. The potential clinical efficacy of caspofungin awaits further investigation.